Anti-Inflammatory Potentials of Rendang Seasoning (Sumatran Traditional Food) Water Extract in RAW264.7 Cells and Mouse Peritoneal Macrophages - Sellen Gurusmatika; Ishida, Momoko; Nishi, Kosuke; Sugahara, Takuya (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2023)
Rendang, one of the most Indonesian traditional seasonings, is composed of many kinds of spices as well as ingredients. Food with rich spice components is gaining recognition as healthy food, because each spice contains many bioactive compounds and has health-promoting potentials, such as anti-inflammation, anti-allergy, and anti-obesity. Hence, the anti-inflammatory potential of rendang seasoning water extract (RSE) was elucidated in this experiment. RSE inhibited nitric oxide, IL-6, and TNF-α production of RAW264.7 cells and P-mac (peritoneal macrophages) with lipopolysaccharide (LPS)-stimulated by suppressing the gene expression levels in a dose-dependent manner. Moreover, inhibition of p38, ERK and JNK as part of mitogen-activated protein (MAP) kinase pathways result in down regulation of RSE, and also translocation of NF-κB to the nucleus from the cytosol. Water extracts of six spices contained in rendang such as clove, cinnamon, white pepper, garlic, red chili, and ginger suppressed cytokines IL-6 and TNF-α production by RAW264.7 cells with LPS-stimulated. It was suggested that the anti-inflammatory effect of rendang is contributed by the anti-inflammation substances in its spice components. Overall findings indicated that rendang has the potential to contribute to anti-inflammation.